Do Code of Points in men artistic gymnastics and women artistic gymnastics favor asymmetric elements? - Ivan ČUK (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2016)
Abstract The purpose of research was to determine whether Code of Point (COP) in Men Artistic Gymnastics (MAG) and Women Artistic Gymnastics (WAG) favor asymmetric elements in order to build gymnast's competition exercise. All elements which are described in MAG (N = 993) and WAG (N = 713) COP were included and defined if they are symmetric at start position, during movement and at final position. Element is symmetric by arms and trunk with legs activity when all left and right body side performs simultaneously same activity. Results show in MAG COP as a whole is significantly more asymmetric elements with asymmetric trunk and legs activity. In WAG COP as a whole is significantly more asymmetric elements with asymmetric activity of arms, trunk and legs. Hypothetical most difficulty exercises on each apparatus revealed that in general for all around gymnast proportion between asymmetric and symmetric elements is close to 70% to 30%, what suggests that difficulty relates to increased asymmetry. COP in MAG and WAG enforces asymmetric movements for achieving high results, however, coaches' task is to be aware of COP influence on gymnasts' health and minimize asymmetries in load and to work on symmetric conditioning.